2016
DOI: 10.4103/0970-9290.183131
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol, a health hazard during ultrasonic scaling: A clinico-microbiological study

Abstract: The aerosols and splatters produced during dental procedures have the potential to spread infection to dental personnel. Therefore, proper precautions should be taken to minimize the risk of infection to the operator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 0 publications
1
25
0
2
Order By: Relevance
“…Moreover, if saliva were the source of microbiota in dental aerosols, one would expect a certain level of microbial heterogeneity between the studies. However, the bacteria most frequently identified in all studies were Staphylococcus aureus, beta hemolytic Streptococci, Escherichia coli, spore-forming bacteria, fungi belonging to the genera Cladosporium and Penicillium, and Micrococccus 66,[79][80][81] ; all of which are environmental species. In parallel, a study of dental unit water reservoirs revealed the presence of 82 Another study documented the presence of high levels (10 5 CFUs) of Legionella, Pseudomonas and non-tuerculous mycobacteria in water lines.…”
Section: Is Saliva the Primary Source Of Pathogens In Dental Aerosols?mentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, if saliva were the source of microbiota in dental aerosols, one would expect a certain level of microbial heterogeneity between the studies. However, the bacteria most frequently identified in all studies were Staphylococcus aureus, beta hemolytic Streptococci, Escherichia coli, spore-forming bacteria, fungi belonging to the genera Cladosporium and Penicillium, and Micrococccus 66,[79][80][81] ; all of which are environmental species. In parallel, a study of dental unit water reservoirs revealed the presence of 82 Another study documented the presence of high levels (10 5 CFUs) of Legionella, Pseudomonas and non-tuerculous mycobacteria in water lines.…”
Section: Is Saliva the Primary Source Of Pathogens In Dental Aerosols?mentioning
confidence: 98%
“…The quantity of sprays, spatter, or aerosol generated by ultrasonics, the distance travelled by the aerosolized particles and their composition have been studied using air samplers, [58][59][60] bacterial growth medium placed at strategic locations, [58][59][60][61][62][63][64][65][66][67] filter paper strips (with and without dye) on the patient and operator, 68,69 and heme-detectors. 70 Sprays are generated during all types of procedures using ultrasonic instruments, whether it be supragingival scaling, subgingival scaling of periodontally diseased teeth or endodontic instrumentation.…”
Section: Ultrasonic Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Corona virus in aerosols can stay viable for 3 hours and travel up to several meters, found in a study [7]. To reduce the risk of infection from aerosol microbiota, it is recommended to do preprocedural rinses, routine sterilization and disinfection, flushing of water supply every 30 patients etc [8].…”
Section: Dental Aerosolmentioning
confidence: 99%